Composition for electrode insulating coating and electrode using same
The electrode insulating coating composition, featuring boehmite particles and a dispersant with multiple fatty acid compounds, addresses the dispersibility issues of conventional compositions, resulting in enhanced heat resistance and adhesion, thereby improving battery safety.
Patent Information
- Application Number
- JP2023547125
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-11-01
- Filing Date
- 2022-10-31
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2042-10-31
AI Technical Summary
Conventional electrode insulating layers using inorganic particles face issues with insufficient dispersibility, leading to non-uniform distribution and reduced heat resistance, which can compromise battery safety.
An electrode insulating coating composition is developed using boehmite particles and a dispersant containing two or more types of fatty acid compounds, which improves the dispersibility and adhesion of the inorganic particles, enhancing the insulating performance and safety of the battery.
The composition achieves excellent insulation performance even under high temperature conditions, maintains adhesion to the electrodes after electrolyte impregnation, and improves battery safety by preventing detachment of the insulating coating layer.
Smart Images

Figure 0007674496000003 
Figure 0007674496000004 
Figure 0007674496000001
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0148086 filed on November 1, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a composition for electrode insulating coating and an electrode using the same, and more particularly to a composition for electrode insulating coating produced by adding boehmite particles and a dispersant containing two or more fatty acid compounds, and an electrode using the same. [Background technology]
[0003] In recent years, as the technological development and demand for mobile devices increases, the demand for batteries as energy sources has increased rapidly, and therefore, research into batteries that can meet various demands has been extensively conducted. In particular, research into lithium secondary batteries that have high energy density as well as excellent life and cycle characteristics as a power source for such devices has been actively conducted.
[0004] A lithium secondary battery includes a positive electrode including a positive electrode active material capable of inserting / desorbing lithium ions, a negative electrode including a negative electrode active material capable of inserting / desorbing lithium ions, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. The positive electrode and the negative electrode have a structure in which an electrode active material layer is formed on one or both sides of an electrode current collector, and in recent years, a technology for forming an insulating layer on the outer periphery of the electrode active material layer has been developed to improve the stability of the electrode. By forming an insulating layer on the outer periphery of the electrode active material layer, the electrode active material layer can be protected from heat generated during the operation of the electrode, and the insulation between the electrodes can be improved.
[0005] Conventional electrode insulating layers have generally been formed using binders with insulating properties. However, because the binder has poor heat resistance, conventional insulating layers made of binders have a problem in that their adhesive strength decreases under high temperature conditions caused by the operation of the battery, which reduces the safety of the battery. To solve this problem, a technology has been proposed in which inorganic particles are added to a coating composition for electrode insulation to improve the heat resistance of the insulating layer.
[0006] However, the electrode insulating coating composition containing inorganic particles proposed so far has a problem that the inorganic particles are not sufficiently dispersible. If the inorganic particles are not smoothly dispersed in the coating composition, the inorganic particles settle to the bottom of the coating composition, and the inorganic particles cannot be uniformly distributed in the insulating layer after the insulating layer is formed, so that the effect of improving heat resistance may be reduced. In addition, in this case, the inorganic particles are distributed intensively at the bottom of the insulating layer, and therefore the content of the binder located at the bottom of the insulating layer is reduced, and the insulating layer is easily detached from the electrode. Furthermore, when the inorganic particles are not effectively dispersed, the inorganic particles aggregate with each other to form particles having a large particle size, which increases the viscosity of the composition, and therefore the thickness and / or surface of the insulating layer may be formed unevenly. Ultimately, such a problem may cause a deterioration in the insulating performance of the insulating layer and a decrease in the safety of the battery. Therefore, there is a demand for a technique that can uniformly disperse the inorganic particles in the insulating layer. Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide an electrode insulating coating composition having improved dispersibility of inorganic particles, an insulating coating layer having excellent coatability and adhesiveness, and an electrode including the insulating coating layer.
[0008] The object of the present invention is not limited to the above-mentioned objects, and other objects not mentioned herein will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]
[0009] According to one embodiment, the present invention provides a composition for electrode insulating coating, comprising boehmite particles, a dispersant, a binder, and a solvent, the dispersant including two or more fatty acid compounds being included in an amount of 1.2 to 8.8 parts by weight based on 100 parts by weight of the boehmite particles.
[0010] According to another embodiment, the present invention provides an electrode comprising a current collector, an electrode active material layer, and an insulating coating layer, the electrode active material layer and the insulating coating layer being disposed on the current collector, and the insulating coating layer being formed from the electrode insulating coating composition described above. Effect of the Invention
[0011] The electrode insulating coating composition according to the present invention contains boehmite particles having excellent heat resistance, and therefore, when an electrode insulating coating layer is formed using the electrode insulating coating composition according to the present invention, excellent insulating performance can be maintained even under high temperature conditions, thereby further improving battery safety.
[0012] In addition, when boehmite particles are used as inorganic particles as in the present invention, the adhesive strength to the electrode is excellent even after immersion in the electrolyte, and detachment of the insulating coating layer can be effectively prevented.
[0013] In addition, the electrode insulating coating composition according to the present invention contains two or more fatty acid compounds as a dispersant, and improves the dispersibility of the boehmite particles, thereby realizing low viscosity characteristics and excellent storage stability and coatability.
[0014] The insulating coating layer formed from the electrode insulating coating composition of the present invention can maintain excellent insulating performance even under high temperature conditions, and has excellent adhesion to the electrode even after immersion in an electrolyte, thereby further improving battery safety. [Brief description of the drawings]
[0015] [Figure 1] 4 is a photograph showing the state of an insulating coating layer formed using the electrode insulating coating composition of Example 2 after being immersed in an electrolyte solution. [Diagram 2] 1 is a photograph showing a state of an insulating coating layer formed using the electrode insulating coating composition of Comparative Example 5 after being immersed in an electrolyte solution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The advantages and features of the present invention, as well as the methods for achieving them, will become apparent from the following detailed description of the embodiments in conjunction with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below, and may be realized in various different forms. The embodiments are provided solely for the purpose of making the disclosure of the present invention complete and fully conveying the scope of the invention to those skilled in the art to which the present invention pertains. The present invention is defined solely by the scope of the claims. The same reference numerals refer to the same elements throughout the specification.
[0017] Unless otherwise defined, all terms (including technical and scientific terms) used in this specification may be used as commonly understood by those having ordinary skill in the art to which the present invention belongs. Furthermore, terms defined in commonly used dictionaries are not to be interpreted ideally or excessively unless otherwise clearly defined.
[0018] The terms used in this specification are for describing the embodiments and are not intended to limit the present invention. In this specification, the singular form includes the plural form unless otherwise specified in the phrase. The terms "including," "having," and "comprising" used in the specification do not exclude the presence or addition of one or more other components in addition to the components mentioned.
[0019] In this specification, when a part includes a certain component, this means that it may further include other components, not excluding other components, unless specifically stated to the contrary.
[0020] In this specification, the phrase "A and / or B" means A, or B, or A and B. In this specification, "%" means % by weight, unless expressly indicated otherwise.
[0021] In this specification, the average particle size (D 50 The average particle size (D) can be defined as the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve. 50 ) can be measured, for example, by using a laser diffraction method. The laser diffraction method generally allows measurement of particle sizes from the submicron range to about several mm, and can provide results with high reproducibility and high resolution.
[0022] The present invention will be specifically described below. Electrode insulating coating composition The electrode insulating coating composition according to one embodiment of the present invention includes boehmite (γ-AlO(OH)) particles, a dispersant, a binder, and a solvent, and the dispersant includes two or more fatty acid compounds and is included in an amount of 1.2 to 8.8 parts by weight based on 100 parts by weight of the boehmite particles.
[0023] Hereinafter, each component of the electrode insulating coating composition according to the present invention will be described. (1) Boehmite particles The boehmite particles are included in the electrode insulating coating composition to increase the heat resistance of the insulating coating layer. Inorganic particles such as boehmite do not soften or melt even at high temperatures, for example, at high temperatures of 900° C. or higher, so that when such inorganic particles are included in the electrode insulating layer, the electrode insulating properties can be maintained even at very high temperatures.
[0024] It is clear that when boehmite particles are used as inorganic particles, the adhesive strength with the current collector after immersion in the electrolyte is superior to that when other inorganic particles (e.g., alumina) are used. This effect is believed to be due to the influence of the hydroxyl group contained in boehmite.
[0025] According to one embodiment of the present invention, the D of the boehmite particles before dissolving in the solvent 50 The D of the boehmite particles before dissolution may be 0.1 μm to 1.0 μm, preferably 0.1 μm to 0.7 μm, and more preferably 0.1 μm to 0.5 μm. 50 When the content of the boehmite particles satisfies the above range, the occurrence of agglomeration of the boehmite particles in the composition is minimized, and an insulating coating layer having a uniform thickness and surface can be formed.
[0026] The boehmite particles may be included in an amount of 10 to 25 parts by weight, preferably 10 to 20 parts by weight, and more preferably 15 to 20 parts by weight, based on 100 parts by weight of the insulating coating composition. When the content of the boehmite particles is within the above range, the occurrence of agglomeration of the boehmite particles is minimized, the viscosity of the insulating coating composition can be appropriately maintained, and an insulating coating layer having a uniform thickness and surface can be formed.
[0027] (2) Dispersant The dispersant is intended to improve the dispersibility of the boehmite particles in the electrode insulating coating composition.
[0028] In the present invention, the dispersant comprises two or more fatty acid compounds. Preferably, the dispersant may contain two or more fatty acids having different carbon numbers. In this case, it has been found that the denseness and thickness of the fatty acid compound layer can be increased, so that the effect of improving dispersibility is even more excellent. In this case, all the fatty acid compounds contained in the dispersant may have different carbon numbers, but this does not necessarily mean that all the fatty acid compounds must be fatty acid compounds having different carbon numbers. For example, when the dispersant contains three or more fatty acid compounds, if two fatty acid compounds have different carbon numbers, the remaining fatty acid compound may have the same carbon number as any one of the two fatty acid compounds, but may be a different type of fatty acid compound.
[0029] According to one embodiment of the present invention, the dispersant may contain a C15-C30 unsaturated fatty acid compound and a C15-C30 saturated fatty acid compound. That is, the dispersant may be a mixture of one or more of the C15-C30 unsaturated fatty acid compounds and one or more of the C15-C30 saturated fatty acid compounds. In other embodiments, the dispersant may contain only two or more types of unsaturated fatty acid compounds, or may contain only two or more types of saturated fatty acid compounds.
[0030] The C15 to C30 unsaturated fatty acid compound is oleic acid (C 18 H 34 O2), Palmitoleic acid (C 16 H 30 O2), Cis-Heptadecenoic acid (C 17 H 32 O2), Vaccenic acid, C 18 H 34 O2), Elaidic acid (C 18 H 34 O2), Linolenic acid (C 18 H 32 O2), arachidonic acid (C 20 H32 O2), Eicosanoic acid (C 20 H 40 O2), Erucic acid (C 22 H 42 O2), eicosapentaenoic acid (EPA, C 20 H 30 O2), docosahexaenoic acid (DHA, C 22 H 32 O2), and Nervonic acid (C 24 H 46 O2).
[0031] The C15 to C30 saturated fatty acid compound is palmitic acid (C 16 H 32 O2), stearic acid (C 18 H 36 O2), arachidic acid (C 20 H 40 O2), behenic acid (C 22 H 44 O2), and lignoceric acid (C 24 H 48 O2).
[0032] According to one embodiment of the present invention, the dispersing agent may include oleic acid, stearic acid, palmitic acid, and nervonic acid.
[0033] The oleic acid is a C18 unsaturated fatty acid having the chemical formula C 18 H 34 It can be represented as O2 and is a fatty acid called oleic acid. As a monounsaturated fatty acid, it has one double bond between carbon atoms and all the remaining carbon atoms are single bonds.
[0034] Nervonic acid is a C24 unsaturated fatty acid and is also expressed as a chain product of oleic acid. Like oleic acid, as a monounsaturated fatty acid, it has one double bond between carbon atoms and all remaining carbon atoms are single bonds.
[0035] The stearic acid is a C18 saturated fatty acid having the chemical formula C 18 H 36 It can be represented as O2. The palmitic acid is a C16 saturated fatty acid having the chemical formula C 16 H 32 It can be represented as O2.
[0036] For example, the dispersant may contain a mixture of fatty acid compounds mixed in a weight ratio of oleic acid:stearic acid:palmitic acid:nervonic acid=(5-25):(5-25):(5-25):(5-25), preferably a weight ratio of (5-15):(5-15):(5-15):(5-15):(5-15), more preferably a weight ratio of oleic acid:stearic acid:palmitic acid:nervonic acid=(9-10):(9-10):(9-10):(8-9). A dispersant containing such a mixture of fatty acid compounds can form a uniform and dense fatty acid compound layer on the surface of the boehmite particles, and further improve the dispersibility of the boehmite particles.
[0037] According to the research of the present inventors, it has become clear that when two or more fatty acid compounds are used as dispersants in a composition containing boehmite particles, the dispersibility of the boehmite particles is significantly improved, and the viscosity and aging characteristics of the electrode insulating coating composition are significantly improved.
[0038] This effect is believed to be due to electrostatic repulsion and steric hindrance between fatty acid compounds that form a layer on the surface of boehmite particles as a result of the hydrocarbon moiety constituting the fatty acid compounds being adsorbed onto the surface of the boehmite particles.
[0039] However, when only one type of fatty acid compound is used as a dispersant, there is no effect of preventing the aggregation of boehmite particles, and the phenomenon occurs in which the boehmite particles aggregate more than when no dispersant is used. Specifically, when a dispersant containing only one type of fatty acid compound is used, although a fatty acid compound layer is formed, it cannot be formed uniformly, and it may induce aggregation between inorganic particles more than when no fatty acid compound is used as a dispersant.
[0040] Meanwhile, the dispersant may be included in an amount of 1.2 to 8.8 parts by weight, preferably 1.2 to 7.6 parts by weight, more preferably 1.4 to 7.0 parts by weight, based on 100 parts by weight of the boehmite particles. If the content of the dispersant is outside the above range, the coating property of the insulating coating layer and the adhesion to the electrode may be reduced. Specifically, if the dispersant is included in an amount of less than 1.2 parts by weight based on 100 parts by weight of the boehmite particles, the boehmite particles may not be sufficiently dispersed in the composition, and the coating process may not be performed due to aggregated particles, or even if coating is possible, the coating may not be formed uniformly, resulting in line defects. Also, if the dispersant is included in an amount of more than 8.8 parts by weight based on 100 parts by weight of the boehmite particles, craters may be generated due to air bubbles during the formation of the coating layer, and the adhesive force between the insulating coating layer and the current collector after immersion in the electrolyte may be reduced, resulting in detachment of the insulating coating layer.
[0041] (3) Binder The binder, in turn, serves to adhere the insulating coating layer to the current collector and / or the electrode active material layer.
[0042] The binder may be formed from a compound of components that are not easily dissolved by the electrolyte of the secondary battery. The binder is not particularly limited as long as it is a polymer binder used in the art, and representative examples thereof include aqueous or non-aqueous polymers including a single member or a mixture of two or more members selected from the group consisting of polyvinylidene fluoride (PVdF), polyvinylidene fluoride-hexafluoropropylene, polyvinylpyrrolidone, polyacrylonitrile, polyvinylidene fluoride-trichloroethylene, polyvinylidene fluoride-chlorotrifluoroethylene (PVdF-CTFE), polymethyl methacrylate, polyvinyl acetate, ethylene-co-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, styrene butadiene copolymer (Styrene Butadiene Rubber, SBR), acrylonitrile styrene butadiene copolymer, and polyimide. Among these, polyvinylidene fluoride (PVdF) is particularly preferable.
[0043] The binder may be included in an amount of 1 to 5 parts by weight, preferably 1 to 3 parts by weight, more preferably 1.5 to 3 parts by weight, based on 100 parts by weight of the electrode insulating coating composition. When the content of the binder is within the above range, excellent adhesion between the insulating coating layer and the electrode is exhibited.
[0044] (4) Solvent Next, the solvent is for dissolving the boehmite particles, the dispersant, and the binder, and for ensuring the coatability of the insulating coating layer formed from the composition.
[0045] The solvent is preferably capable of dissolving the boehmite particles, the dispersant, and the binder to a certain level or more, but is a non-solvent for the electrode active material layer.
[0046] Specific examples of the solvent include acetone, tetrahydrofuran, acetonitrile, dimethylformamide, dimethylsulfoxide, dimethylacetamide, and N-Methyl-2-Pyrrolidone (NMP), which may be used alone or in combination of two or more. Among these, N-Methyl-2-Pyrrolidone (NMP), which is suitable for dissolving non-aqueous binders (e.g., polyvinylidene fluoride), is particularly preferred.
[0047] The solvent may be included in an amount that allows the composition to have a suitable viscosity in consideration of the coating properties of the composition, for example, 70 to 90 parts by weight, preferably 75 to 85 parts by weight, based on 100 parts by weight of the composition. Preferably, the electrode insulating coating composition according to the present invention may have a solid content of 10 to 30% by weight, preferably 15 to 25% by weight, more preferably 17 to 23% by weight. When the solid content satisfies the above range, the composition may have a suitable viscosity for forming a coating layer while minimizing the occurrence of agglomeration of boehmite particles in the composition.
[0048] The electrode insulating coating composition of the present invention as described above can be prepared by mixing boehmite particles, a dispersant, and a binder in a solvent and then performing a dispersion process.
[0049] First, the boehmite particles, the dispersant, and the binder are mixed in a solvent to mix the components of the composition. In this case, the mixing may be performed using a mixing device known in the art, such as, but not limited to, a homo mixer.
[0050] Next, the composition that has undergone the mixing process is milled to disperse the mixture. The milling may be performed using a ball mill, a bead mill, or a basket mill, and more specifically, may be performed using a bead mill.
[0051] Meanwhile, the degree of dispersion of the composition can be adjusted by adjusting milling conditions such as the number of passes (hereinafter, “number of passes”) of the composition through the ball mill, bead mill, or basket mill, and rotor speed.
[0052] According to one embodiment of the present invention, the D of the solid particles in the composition 50 may be 0.4 μm to 1.3 μm, preferably 0.4 μm to 1.0 μm, more preferably 0.4 μm to 0.7 μm. Here, the solid particles may include at least one of boehmite particles, a dispersant, and a binder. Specifically, the solid particles may be in a form in which the boehmite particles are bound to each other, or in a form in which the boehmite particles are bound to the dispersant and / or the binder.
[0053] When the particle size of the solid particles in the composition satisfies the above range, the dispersibility of the boehmite particles in the composition is improved, and the coatability and adhesiveness of the insulating coating layer can be significantly improved.
[0054] Meanwhile, the degree of dispersion of the solid particles in the composition can be adjusted by adjusting the solid content in the composition, the type and content of the dispersant, and / or the dispersion process conditions.
[0055] electrode Next, an electrode including the insulating coating layer according to the present invention will be described. The electrode includes a current collector, an electrode active material layer, and an insulating coating layer. The electrode active material layer and the insulating coating layer may be disposed on the current collector. In this case, the insulating coating layer may be formed from the electrode insulating coating composition described above.
[0056] The current collector only needs to be one that does not induce chemical changes in the battery and has conductivity, and is not particularly limited. For example, as the current collector, copper, stainless steel, aluminum, nickel, titanium, fired carbon, or those obtained by surface treatment of the surface of aluminum or stainless steel with carbon, nickel, titanium, silver, etc. may be used.
[0057] Next, the electrode active material layer may be a positive electrode active material layer containing a positive electrode active material or a negative electrode active material layer containing a negative electrode active material. As the positive electrode active material, positive electrode active materials well-known in the technical field may be used without limitation. For example, lithium cobalt-based oxides, lithium nickel-based oxides, lithium manganese-based oxides, lithium iron phosphate, lithium nickel manganese cobalt-based oxides, or combinations thereof may be used. Specifically, as the positive electrode active material, LiCoO2, LiNiO2, LiMn2O4, LiCoPO4, LiFePO4, and LiNi a Mn b Co c O2 (where 0 < a, b, c < 1) etc. may be used, but are not limited thereto.
[0058] As the negative electrode active material, natural graphite, artificial graphite, carbonaceous materials; lithium-containing titanium composite oxides (LTO), Si, Sn, Li, Zn, Mg, Cd, Ce, Ni, or metals such as Fe (Me); alloys composed of the metals (Me); oxides of the metals (MeO x ); and one or more negative electrode active materials selected from the group consisting of composites of the metals (Me) and carbon may be mentioned.
[0059] On the other hand, the electrode active material layer may further contain a conductive material and a binder in addition to active materials such as a positive electrode active material and a negative electrode active material. The conductive material is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and examples thereof include graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives. Specific examples of commercially available conductive materials include acetylene black-based products (Chevron Chemical Company, Denka Singapore Private Limited, Gulf Oil Company products, etc.), Ketjenblack, EC-based products (Armak Company products), Vulcan XC-72 (Cabot Company products), and Super P (Timcal).
[0060] The binder is a component that aids in binding the active material to the conductive material and the current collector, and is usually added in an amount of 1 to 30% by weight based on the total weight of the mixture containing the positive electrode active material. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butylene rubber, fluororubber, and various copolymers.
[0061] Next, the insulating coating layer is formed by applying the above-mentioned electrode insulating coating composition onto the current collector and then drying it. The insulating coating layer may be formed on a non-coated portion of the current collector where the electrode active material layer is not formed, and in this case, the insulating coating layer may be formed to partially overlap an end of the electrode active material layer.
[0062] The insulating coating layer may be formed to a constant thickness on the current collector and the electrode active material layer. In this case, the thickness of the insulating coating layer may be 10 μm to 30 μm, preferably 15 μm to 25 μm, and more preferably 17 μm to 23 μm. When the thickness of the insulating coating layer satisfies the above range, the adhesion of the insulating coating layer to the current collector and / or the electrode active material layer may be further improved.
[0063] Meanwhile, the insulating coating layer according to one embodiment of the present invention has excellent coatability and adhesion compared to conventional insulating coating layers. Specifically, the insulating coating layer has excellent coatability because it has a uniform thickness and / or surface. In addition, the boehmite particles are uniformly dispersed on the insulating coating layer, and a sufficient amount of binder is present at the bottom of the insulating coating layer, so that the insulating coating layer has excellent adhesion.
[0064] The present invention will be described in more detail with reference to the following examples, however, the following examples are for illustrative purposes only and are not intended to limit the scope of the present invention.
[0065] Example 1 BYK-P104 manufactured by BYK was prepared as a dispersant. The BYK-P104 contains 50 parts by weight of a mixture of fatty acid compounds in which oleic acid, stearic acid, palmitic acid, and nervonic acid are mixed in a weight ratio of (9-10):(9-10):(9-10):(8-9) based on the total weight, and 50 parts by weight of a solvent in which xylene, ethylbenzene, and isobutyl ketone are mixed in a ratio of 65:27:8 based on the total weight.
[0066] In 80 parts by weight of NMP solution as a solvent, 500.2μm, specific surface area 17m 2 17 parts by weight of 1 / g boehmite (product name: ACTILOX200SM, manufacturer: Nabaltec), 0.3 parts by weight of BYK-P104 (product name) as a dispersant, and 2.7 parts by weight of PVdF (product name: KF9700, manufacturer: KUREHA) as a binder were mixed to produce 1 kg of a mixture, which was then mixed for 1 hour using a homomixer (product name: Dispermat LC, manufacturer: VMA).
[0067] Next, a dispersion process was performed using a Bead Mill (product name: LS-1, manufacturer: NETZSCH) with a rotor speed of 3300 RPM, a discharge amount of 540 g / min per pass, and 7 passes to prepare a composition for electrode insulating coating.
[0068] Example 2 An electrode insulating coating composition was prepared in the same manner as in Example 1, except that 0.6 parts by weight of the dispersant and 2.4 parts by weight of the binder were mixed and the dispersion process was carried out with 6 passes.
[0069] Example 3 An electrode insulating coating composition was prepared in the same manner as in Example 1, except that 1 part by weight of the dispersant and 2 parts by weight of the binder were mixed and the dispersion process was carried out with 4 passes.
[0070] Example 4 An electrode insulating coating composition was prepared in the same manner as in Example 2, except that the dispersion process was performed with 8 passes.
[0071] Example 5 An electrode insulating coating composition was prepared in the same manner as in Example 2, except that the dispersion process was performed with 4 passes.
[0072] Comparative Example 1 An electrode insulating coating composition was prepared in the same manner as in Example 4, except that no dispersant was used and 3 parts by weight of binder was mixed.
[0073] Comparative Example 2 An electrode insulating coating composition was prepared in the same manner as in Example 4, except that H-NBR (product name: THERBAN 3400, manufacturer: ARLANXEO) was used as a dispersant instead of BYK-P104.
[0074] Comparative Example 3 An electrode insulating coating composition was prepared in the same manner as in Example 4, except that 0.1 parts by weight of the dispersant and 2.9 parts by weight of the binder were mixed.
[0075] Comparative Example 4 An electrode insulating coating composition was prepared in the same manner as in Example 3, except that 2 parts by weight of the dispersant and 1 part by weight of the binder were mixed.
[0076] Comparative Example 5 An electrode insulating coating composition was prepared in the same manner as in Example 2, except that alumina (product name: AES-11, manufacturer: Sumitomo) was used instead of boehmite as the inorganic particles.
[0077] [Table 1]
[0078] Experimental Example 1 - Particle size measurement Using a particle size analyzer (product name: MASTERSIZER 3000, manufacturer: Malvern), the particle size D of the particles in the electrode insulating coating compositions prepared in Examples 1 to 5 and Comparative Examples 1 to 5 was measured. 10 , D 50 , and D. 90 The measurement results are shown in Table 2 below.
[0079] Experimental Example 2 - Viscosity Measurement The viscosity of each of the electrode insulating coating compositions prepared in Examples 1 to 5 and Comparative Examples 1 to 5 was measured, and the measurement results are shown in Table 2 below. The viscosity of the composition was measured using a viscometer (product name: viscometer TV-22, manufacturer: TOKI) at 25° C. and 1 rpm.
[0080] Experimental Example 3 - Evaluation of storage stability (cohesion) The electrode insulating coating compositions prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were stored in 50 ml vials for 24 hours, and then the occurrence of precipitation was visually observed and evaluated as follows. The evaluation results are shown in Table 2. ○: No precipitation occurs ×: Precipitation occurs
[0081] Experimental Example 4 - Evaluation of Coating Properties The electrode insulating coating compositions prepared in Examples 1 to 5 and Comparative Examples 4 to 5 were coated on aluminum foil to a thickness of 20 μm and then dried to form insulating coating layers.
[0082] The formed insulating layer was visually observed to check for defects and was evaluated as follows. The evaluation results are shown in Table 2 below. ○: No line defects or craters due to air bubbles were observed. ×: Poor line quality or craters caused by air bubbles are observed On the other hand, the electrode insulating coating compositions of Comparative Examples 1 to 3 had excessively high viscosities, making it impossible to form an insulating coating layer by coating.
[0083] Experimental Example 5 - Evaluation of Adhesion The electrode insulating coating compositions prepared in Examples 1 to 5 and Comparative Examples 4 to 5 were coated on aluminum foil to a thickness of 20 μm, then dried to form an insulating coating layer, which was then cut into 20 mm×100 mm pieces and immersed in an electrolyte (LiPF61M, EC / EMC=3 / 7 (vol%)) at 60° C. for 24 hours. The presence or absence of detachment from the aluminum foil substrate was checked with the naked eye and evaluated as follows. The evaluation results are shown in Table 2.
[0084] ○: No detachment or lifting occurs ×: Detachment or floating occurs On the other hand, the electrode insulating coating compositions of Comparative Examples 1 to 3 had excessively high viscosities, making it impossible to form an insulating coating layer by coating.
[0085] FIG. 1 is a photograph showing the state of an insulating coating layer formed using the electrode insulating coating composition of Example 2 after being immersed in an electrolyte, and FIG. 2 is a photograph showing the state of an insulating coating layer formed using the electrode insulating coating composition of Comparative Example 5 after being immersed in an electrolyte.
[0086] From Figures 1 and 2, it can be seen that the insulating coating layer formed from the electrode insulating coating composition of Example 2 using boehmite as the inorganic particles maintained the coating layer without detachment or floating even after impregnation with the electrolyte, whereas the insulating coating layer formed from the electrode insulating coating composition of Comparative Example 5 using alumina detached and floated after impregnation with the electrolyte.
[0087] [Table 2]
[0088] From Table 2, it can be seen that the electrode insulating coating compositions of Examples 1 to 5, which use boehmite as inorganic particles and two or more fatty acid compounds as dispersants in an amount of 1.2 to 8.8 parts by weight per 100 parts by weight of the boehmite particles, have less particle aggregation in the composition, excellent storage stability, and excellent coating properties. In addition, it can be seen that when an insulating coating layer is formed from the electrode insulating coating compositions of Examples 1 to 5, excellent adhesive strength is maintained even after immersion in an electrolyte solution.
[0089] In contrast, the electrode insulating coating composition of Comparative Example 1, which did not use a dispersant, experienced severe particle aggregation in the composition, which resulted in an excessively high viscosity, making it impossible to carry out the coating process.
[0090] In addition, the electrode insulating coating composition of Comparative Example 2 using H-NBR as a dispersant showed lower particle aggregation and viscosity than Comparative Example 1, but the viscosity was still too high, making it impossible to carry out the coating process.
[0091] Meanwhile, in the case of the electrode insulating coating compositions of Comparative Examples 3 and 4, in which the dispersant content of the electrode insulating coating composition was outside the range of the present invention, the coating property, adhesion, and / or storage stability were deteriorated.
[0092] In addition, as shown in FIG. 2 and Table 2, when an insulating coating layer was formed using the electrode insulating coating composition of Comparative Example 5, which used alumina instead of boehmite as inorganic particles, the adhesive strength with the current collector after immersion in the electrolyte solution was significantly reduced.
Claims
1. Boehmite particles; A dispersant; Binder and A solvent; Including, The dispersing agent includes oleic acid, stearic acid, palmitic acid, and nervonic acid, and is included in an amount of 1.2 to 8.8 parts by weight based on 100 parts by weight of the boehmite particles.
2. 2. The electrode insulating coating composition according to claim 1, wherein the oleic acid, the stearic acid, the palmitic acid and the nervonic acid are contained in a weight ratio of (5-25):(5-25):(5-25):(5-25).
3. 2. The electrode insulating coating composition according to claim 1, wherein the binder is polyvinylidene fluoride.
4. 2. The electrode insulating coating composition according to claim 1, wherein the solvent is at least one selected from the group consisting of acetone, tetrahydrofuran, acetonitrile, dimethylformamide, dimethylsulfoxide, dimethylacetamide, and N-methyl-2-pyrrolidone (NMP).
5. For 100 parts by weight of the electrode insulating coating composition, 10 to 25 parts by weight of the boehmite particles; 0.2 to 1.5 parts by weight of the dispersant; 1 to 5 parts by weight of the binder; The electrode insulating coating composition according to claim 1, further comprising 70 to 90 parts by weight of the solvent.
6. 2. The electrode insulating coating composition according to claim 1, wherein the electrode insulating coating composition has a solid content of 10% by weight to 30% by weight.
7. A current collector, an electrode active material layer, and an insulating coating layer are included, the electrode active material layer and the insulating coating layer are disposed on the current collector; An electrode, wherein the insulating coating layer is formed from the electrode insulating coating composition according to claim 1 .
Citation Information
Patent Citations
Coating composition for separator, method for preparing separator using the same, and separator and lithium battery employing the separator
US20210288383A1